An Integrative Framework Capturing Kyai Charismatic Leadership And Madura Society Welfare Level In East Java - Indonesia. - ., Kuswandi; ., Ujianto; Kusmaningtyas, Amiartutik (Archives of Business Research, 2016)
Objectives - The models used in the empirical study of leadership kyai in Madura ethnic in line with the more modern environment changes. Reflecting the environmental change this paper aims to propose a framework for leadership of charismatic kyai in Madura ethnic-based impact on the welfare of stimulus-organism-response (S-O-R) wide. The design / methodology / approach - This paper offers a conceptual framework that integrates the components of the leadership of religious scholars in ethnic Madurese kharismatic. Findings - This framework is useful for academics and regions. This framework can help steer academics to various existing literature charismatic leadership and help researchers development empirical studies that describe ethnic leadership kyai in Madurese. For the professional, this framework can be used as guidance in building a successful region. Research/ Limitations/ implications - This paper does not examine empirically the proposed framework. However, this paper provides suggestions for future research, including reviewing the empirical structural relationships in this framework.